Effects of maternal dietary EPA and DHA supplementation and breeder age on embryonic and post‐hatch performance of broiler offspring: Age and n‐3 pufa affect embryonic and post‐hatch performance. (April 2015) - Koppenol, A.; Delezie, E.; Wang, Y.; Franssens, L.; Willems, E.; Ampe, B.; Buyse, J.; Everaert, N.
Summary: Breeder age and nutrition are amongst the most important factors affecting progeny growth and development. The present experiment was carried out to evaluate the effects of n‐3 fatty acid (FA), with special emphasis on the ratio of eicosapentaenoic (EPA, 20:5 n‐3) and docosahexaenoic (DHA, 22:6 n‐3) acid, provided to the diet of ageing broiler breeder hens at different ratios, on the incubation parameters and the performance of the offspring. Four hundred and eighty Ross‐308 broiler breeder hens were fed one of four different diets (120/treatment), with an equal fat content. The control diet was a basal diet, rich in n‐6 FAs (CON). Blends of fish oil were used to enrich the three other diets in n‐3 FA and to obtain different EPA/DHA ratios of 1/1 (EPA=DHA), 1/2 (DHA) or 2/1 (EPA). Every 5 weeks, incubation parameters were assessed. Every 15 weeks, offspring was reared until slaughter age on a standard diet. Breeder age affected almost all incubation and post‐hatch parameters, whereas n‐3 FA treatment only lowered egg weight (p < 0.0001) and consequently hatched chick weight (p < 0.0001). Supplementation of EPA resulted in a higher proportional liver weight (p = 0.0219) at hatch, a lower body weight up to 28 days post‐hatch (p = 0.0418), a lower daily weight gain (p = 0.0498) and a higher feed conversion ratio (p = 0.0395) during the starter period (p = 0.0498), resulting in a higher overall offspring feed conversion ratio (p = 0.0317) compared to the control diet. DHA supplementation, on the other hand, resulted in a lower residual yolk weight (p = 0.0220) and a higher overall offspring mortality (p = 0.0125). In conclusion, supplementation of n‐3 FA could not counter the adverse effect of breeder flock age, but did not harm incubation or improve post‐hatch performance, either. EPA and DHA affected offspring development differently during early post‐hatch life.